A structured approach to the child with precocious puberty. Issue 5 (May 2022) - Reynolds, Sarah; Easton, Timothy; Assameur, Asma; Ponmani, Caroline
Abstract: Precocious puberty is the appearance of physical and hormonal features of puberty before 8 years (girls) or 9 years (boys). Untreated it limits adult height and has potential psychosocial implications. It is a fairly common referral to secondary care clinics and is often seen by general paediatricians in the first instance in the UK. As an outpatient presentation it can cause anxiety owing to the breadth of potential aetiologies and concerns about missing a rare sinister cause. This short article offers a structured approach to precocious puberty to help identify any sinister causes and determine what steps you should take next.